The impacts of food vlog attributes on para-social interaction and customers' response behaviours / Nurul Iman Abd Razak and Muhammad Izzat Zulkifly. - Abd Razak, Nurul Iman; Zulkifly, Muhammad Izzat (Universiti Teknologi MARA Cawangan Selangor and UiTM Press, 2020)
In the era of globalization that we live in today, technology is not a new thing in our daily life. Foodservice industry today relies on many kinds of technologies for different functions such as ordering, producing, delivering, and even presenting the menu. Foodservice industry grabs this opportunity to evolve especially in the marketing aspects since it is very important to gain customers worldwide and expand the businesses in this new era of modernization. E-commerce is recognized as one of the initiatives to reach customers and gain better information. Online reviews such as food vlogs are parts of e-commerce which are believed to be the current trend among customers. This conceptual paper seeks to understand the food vlog's attributes that lead to para-social interaction and its impacts on customers' recommendation adoption. This area of study is rarely discovered in Malaysia thus it will provide a new knowledge specifically the para-social interaction in relation to the foodservice industry. It will also help the vlogger communities to identify the most influential attributes that keep people watching and believing in their contents and consequently visit the restaurants or consume the food the vloggers' review.